Gastrointestinal Motility and Response to Levodopa in Parkinson's Disease: A Proof‐of‐Concept Study. Issue 10 (15th August 2022) - Safarpour, Delaram; Brumbach, Barbara H.; Arena, Monica; Quinn, Joseph; Diamond, Sarah; Nutt, Jay G.; Pfeiffer, RonaldF.
Abstract: Background: Simultaneous measurement of gastrointestinal transit time (GITT) and plasma levodopa concentration (PLC) is crucial to understanding the effect of dysfunctional motility on levodopa response in patients with Parkinson's disease (PwPD). Objective: The aim is to determine if altered segmental GITT correlates with clinical response and PLC variability in PwPD. Methods: Ten typical and 10 erratic responders ingested the SmartPill (SP) wireless motility capsule. Serial PLC and finger tapping, obtained every 30 minutes for 3 hours after SP/levodopa ingestion, evaluated the correlation between GITT, clinical response, and PLC. Glucose breath testing assessed small intestinal bacterial overgrowth (SIBO). Results: GITT was not significantly different in "typical" and "erratic" responders. SIBO was positive in half of the erratic and negative in most typical responders. Conclusion: SP is a feasible technology for assessing GITT in PwPD. A larger study may be able to significantly differentiate/correlate GITT in different segments of the GI tract with response to levodopa. © 2022 International Parkinson and Movement Disorder Society. Abstract :